1994
DOI: 10.1097/00132586-199412000-00045
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance after Abdominal Surgery

Abstract: A study was carried out to determine the time course and degree of postoperative insulin resistance in patients undergoing elective abdominal surgery. Mean(s.e.m.) insulin sensitivity was determined before and on the first (n= lo), fifth, ninth and 20th (n= 5) days after elective open cholecystectomy using the nonnoglycaemic (4.7(0 1) mmol/l), hyperinsulinaemic (402(12) pmol/l) glucose clamp technique. Preoperative insulin sensitivity expressed as the M value varied from 2.3 to 8-2mg per kg per min. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
13

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 0 publications
2
68
1
13
Order By: Relevance
“…Surgical injury provokes a stress response that leads to a high catabolic state with hyperglycemia and increased oxidation of body protein [20], which is characterized by a state of insulin resistance [21] and can interfere with the postoperative recovery process [22,23]. In recent years, some perioperative protocols, including preoperative oral carbohydrate [24], epidural analgesia, early nasogastric tube removal, and early feeding with a low-fat liquid diet, have all aimed at suppressing perioperative stress to achieve a faster recovery from surgery and a quicker hospital discharge of patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical injury provokes a stress response that leads to a high catabolic state with hyperglycemia and increased oxidation of body protein [20], which is characterized by a state of insulin resistance [21] and can interfere with the postoperative recovery process [22,23]. In recent years, some perioperative protocols, including preoperative oral carbohydrate [24], epidural analgesia, early nasogastric tube removal, and early feeding with a low-fat liquid diet, have all aimed at suppressing perioperative stress to achieve a faster recovery from surgery and a quicker hospital discharge of patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been linked primarily to the invasiveness of surgery. 24,25 Other factors may also contribute, such as the duration of trauma, 26 bed rest and immobilization, 27 type of anesthesia and analgesia, 28,29 nutrition and preoperative fasting, 30,31 blood loss, 25 physical status, and post-surgery rehabilitation. 32 …”
Section: Insulin Resistancementioning
confidence: 99%
“…The second phase of the metabolic response, lasting several weeks after injury, has been termed the "flow phase" (28,46,99,111), although more recent studies indicate that this phase may continue in children for at least a year postburn (46). Initial studies in burned animals indicated that glucose uptake in response to exogenous insulin is decreased (103).…”
Section: Whole Body Changes In Glucose and Fat Metabolism Postburnmentioning
confidence: 99%